Swi6B, an alternative splicing isoform of Swi6, mediates the cell wall integrity of Ganoderma lucidum. (14th June 2021) - Lian, Lingdan; Zhang, Guang; Zhu, Jing; Wang, Yunxiao; Wang, Lingshuai; Liu, Rui; Shi, Liang; Ren, Ang; Zhao, Mingwen
Summary: The cell wall integrity (CWI) signaling activates the transcription factor Swi6 through a MAPK signaling cascade in response to cell wall stresses. In this study, we observed two different mRNA variants of swi6 ( GlSwi6A and GlSwi6B ) existed, due to alternative splicing. Besides, the expression level of GlSwi6B was higher than that of the GlSwi6A mRNA variant. The co‐silencing of GlSwi6A and GlSwi6B was more sensitive to cell wall stress compared with WT, resulting in a decrease of 78% and 76% in chitin and β‐1, 3‐d ‐glucan content respectively. However, only the overexpression of GlSwi6B decreased the sensitivity to cell wall stress and increased the content of chitin and β‐1, 3‐d ‐glucan compared with the WT strain. Furthermore, Y1H, EMSA and BLI assays revealed that the GlSwi6B could bind to the promoters of chitin and glucan synthesis genes (GL24454 and GL18134). However, the binding phenome has not been observed in the isoform GlSwi6A. Taken together, our results found two different transcripts generated from Swi6, in which the alternative splice isoform of GlSwi6B participates in regulating the CWI of G . lucidum . This study provides the first insight into the alternative splicing isoform of GlSwi6B in the regulation of CWI signaling in fungi.